Optimal pooling strategies for nucleic acid testing of donated blood considering viral load growth curves and donor characteristics. Issue 1 (2nd January 2017) - El-Amine, Hadi; Bish, Ebru K.; Bish, Douglas R.
ABSTRACT: Blood products are vital to healthcare, and their safety, in terms of being free of transfusion-transmittable infections (TTIs), is crucial. Unlike serological assays that screen for antibodies and antigens, Nucleic Acid Testing (NAT) technology screens for genetic material, enabling an earlier detection of the infection. However, because NAT is more expensive than serological testing, most blood centers administer NAT to pools of blood samples from multiple donors. This reduces the testing cost, but also decreases the test's sensitivity due to a dilution effect. Further, first-time donors typically have higher prevalence rates than repeat donors, and therefore, a flexible, non-universal strategy which allows first-time donors to undergo more extensive screening may reduce the TTI risk in transfusion recipients. Since some donor characteristics are uncertain, we develop a chance-constrained model that determines the optimal NAT pool sizes for the various TTIs, considering both non-universal and universal (i.e., common testing for all donors) strategies, so as to minimize the TTI risk while remaining within the testing budget with a high probability. Our case study of the United States quantifies the risk reduction benefit of non-universal NAT testing schemes over current practice.